Two new species of Anoplophora Hope, 1839 from China (Coleoptera, Cerambycidae, Lamiinae) - Wang, Cheng-Bin; He, Li; Huang, Jian-Bin (Zootaxa, 2023)
Two new species of starry longhorn beetles are described from China, i.e. Anoplophora iadina sp. nov. from Yunnan and A. zibroides sp. nov. from Hunan and Guangxi. Color plates are presented to illustrate their diagnostic characters.